Rate Cutting Tax Reforms and Corporate Tax Competition in Europe - Friedrich Heinemann; Michael Overesch; Johannes Rincke (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
While there is a large and growing number of studies on the determinants of corporate tax rates, the literature has so far ignored the fact that the behavior of governments in setting tax rates is often best described as a discrete choice decision problem. We set up an empirical model that relates a government's decision whether to cut its corporate tax rate to the country's own inherited tax and taxes in neighboring countries. Using comprehensive data on corporate tax reforms in Europe since 1980, we find evidence suggesting that the position in terms of the tax burden imposed on corporate income relative to geographical neighbors strongly affects the probability of rate cutting tax reforms. Countries are particularly likely to cut their statutory tax rate if the inherited tax is high and if they are exposed to low-tax neighbors.
Keywords: H25; H20; H71; 330; Tax reform; tax competition; corporate taxes; Körperschaftsteuer; Steuerreform; Unternehmensbesteuerung; Steuertarif; Steuerwettbewerb; Diskrete Entscheidung; Europa